Hospital waste management in nonteaching hospitals of Lucknow City, India - Manish Kumar Manar; Krishna Kumar Sahu; Shivendra Kumar Singh (Journal of Family Medicine and Primary Care, 2014)
Objective: To assess hospital waste management in nonteaching hospitals of Lucknow city. Materials and Methods: A cross-sectional, descriptive study was conducted on the staffs of nonteaching hospitals of Lucknow from September 2012 to March 2013. A total of eight hospitals were chosen as the study sample size. Simple random sampling technique was used for the selection of the nonteaching hospitals. A pre-structured and pre-tested interview questionnaire was used to collect necessary information regarding the hospitals and biomedical waste (BMW) management of the hospitals. The general information about the selected hospitals/employees of the hospitals was collected. Results: Mean hospital waste generated in the eight nonteaching hospitals of Lucknow was 0.56 kg/bed/day. About 50.5% of the hospitals did not have BMW department and colored dustbins. In 37.5% of the hospitals, there were no BMW records and segregation at source. Incinerator was used only by hospital A for treatment of BMW. Hospital G and hospital H had no facilities for BMW treatment. Conclusion: There is a need for appropriate training of staffs, strict implementation of rules, and continuous surveillance of the hospitals of Lucknow to improve the BMW management and handling practices.